1999
DOI: 10.1016/s1074-7613(00)80095-3
|View full text |Cite
|
Sign up to set email alerts
|

RAG2:GFP Knockin Mice Reveal Novel Aspects of RAG2 Expression in Primary and Peripheral Lymphoid Tissues

Abstract: We generated mice in which a functional RAG2:GFP fusion gene is knocked in to the endogenous RAG2 locus. In bone marrow and thymus, RAG2:GFP expression occurs in appropriate stages of developing B and T cells as well as in immature bone marrow IgM+ B cells. RAG2:GFP also is expressed in IgD+ B cells following cross-linking of IgM on immature IgM+ IgD+ B cells generated in vitro. RAG2:GFP expression is undetectable in most immature splenic B cells; however, in young RAG2:GFP mice, there are substantial numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
188
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(199 citation statements)
references
References 47 publications
11
188
0
Order By: Relevance
“…Using transgenic mice with a RAG2-GFP fusion gene inserted into the RAG2 locus (RAG2-GFP mice), Gartner et al (73) found that most RAG2 ϩ cells appearing in the SPL after immunization corresponded to migrant pre-B/immature B cells (B220 low CD43 low sIgM low ) from the BM. No GFP expression was detectable in sIgM high transitional splenic B cells or mature B cells (73,74). In transgenic mice with GFP under the control of RAG2 regulatory genes, Yu et al (75) reported that GFP expression does not occur in mature B cells during an immune response although it does occur in immature/transitional splenic B cells (B220 low CD24 ϩ CD93 ϩ ).…”
Section: Rag Expression and L Chain Editing In B Cells Deficient For mentioning
confidence: 99%
“…Using transgenic mice with a RAG2-GFP fusion gene inserted into the RAG2 locus (RAG2-GFP mice), Gartner et al (73) found that most RAG2 ϩ cells appearing in the SPL after immunization corresponded to migrant pre-B/immature B cells (B220 low CD43 low sIgM low ) from the BM. No GFP expression was detectable in sIgM high transitional splenic B cells or mature B cells (73,74). In transgenic mice with GFP under the control of RAG2 regulatory genes, Yu et al (75) reported that GFP expression does not occur in mature B cells during an immune response although it does occur in immature/transitional splenic B cells (B220 low CD24 ϩ CD93 ϩ ).…”
Section: Rag Expression and L Chain Editing In B Cells Deficient For mentioning
confidence: 99%
“…S1A). The use of the RAG2p‐GFP model allows to easily assess de novo thymopoiesis as expression of the GFP transgene, marking newly developed T cells, is controlled by the Rag2 promoter activity (Monroe et al ., 1999; Yu et al ., 1999; Rafei et al ., 2011). Thymic analysis 1 week following the last injection revealed a progressive increase in total thymocyte count in 15M but not 2M‐old rIL‐21‐treated mice with an optimal response rate achieved at a dose of 50 μg kg −1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…38 Most GFP ϩ cells in the spleen were phenotypically identical to pre-B and immature B cells. 38 Our experiments studied the expression of RAG1/GFP in GCs of the Ag-immunized spleen. GFP expression was not detected in the central region of GCs, nor was it down-regulated.…”
Section: Discussionmentioning
confidence: 97%